Childbirth Yesterday and Today: A Comparative Analysis of Women's Experiences and Feelings through the Ages to the Present. (2020) - Bączek, Grażyna; Misztal, Alicja; Kajdy, Anna; Sys, Dorota; Baranowska, Barbara; Jasińska, Joanna
No abstract available